2014
DOI: 10.1179/2045772314y.0000000251
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids’ effect on leptin and adiponectin concentrations in patients with spinal cord injury: A double-blinded randomized clinical trial

Abstract: Context: Omega-3 fatty acids have been recently proposed to induce neural improvement in patients with spinal cord injury (SCI) while affecting some hormones including leptin and adiponectin. Objectives: We tried to evaluate the effect of omega-3 fatty acids on circulatory concentrations of leptin and adiponectin among these patients. Design: This study is a double-blinded randomized clinical trial with intervention duration of 14 months. Setting: A tertiary rehabilitation center. Participants: Total of 104 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Completeness was classified as either complete (no preserved sensory or motor function) or incomplete (variable preserved motor function). 18,19 American Spinal Cord Injury Association Scale (ASIA) was used to classify patients as follows: ASIA-A: complete injury; ASIA-B: incomplete injury with preserved sensory function; ASIA-C: preserved motor function in which more than half of key muscles below the neurological level have a muscle grade < 3; ASIA-D: preserved motor function in which at least half of key muscles below the neurological level have a muscle grade of ≥ 3.…”
Section: Clinical and Neurological Assessmentmentioning
confidence: 99%
“…Completeness was classified as either complete (no preserved sensory or motor function) or incomplete (variable preserved motor function). 18,19 American Spinal Cord Injury Association Scale (ASIA) was used to classify patients as follows: ASIA-A: complete injury; ASIA-B: incomplete injury with preserved sensory function; ASIA-C: preserved motor function in which more than half of key muscles below the neurological level have a muscle grade < 3; ASIA-D: preserved motor function in which at least half of key muscles below the neurological level have a muscle grade of ≥ 3.…”
Section: Clinical and Neurological Assessmentmentioning
confidence: 99%
“…Rats on the HFC diet and fructose drinking water had blood insulin and leptin levels twice as much as those on the LFC improves insulin sensitivity. Dietary supplementation of n-3 PUFA, in particular EPA and DHA, increases the serum concentration of adiponectin in humans and animals (Gray et al, 2013;Sabour et al, 2015). Recent reports demonstrated that replacing saturated fatty acids with n-3…”
Section: Shrimp Oil Improved Serum Lipid Profilementioning
confidence: 99%
“…The median number of individuals with SCI was 15 (range: 4‐558, interquartile range: 10‐32), the median total sample size was 18 (range: 4‐582, interquartile range: 10‐34), see Figure . The subset of studies with a total sample size >100 (n = 12) comprised multicenter as well as single‐center trials . We found that 167 out of 207 (81%) eligible studies met our definition of a small‐sample size study.…”
Section: Resultsmentioning
confidence: 97%